المعاهدات المتتالية المتصلة بموضوع واحد (El-Wahat Journal for Research and Studies, 2015)
International Treaty is an agreement between two or more States in order to lay the foundations for joint work in one of the fields governed by international law and international relations.   The importance of the international treaty emerges as important legal tool of correlation and legal contract between the subjects of international law, whether at the regional or international level, but the subject of international treaties may be unified addressing the same subject and here we wonder: Are the successive treaties that deal with the same subject of the treaty that preceded it  considered as modified, copied or reticence version to the earlier treaty?   However, these conventions have not brought all solutions relating to practical problems posed by the subject of international Successive Treaties. Key Words: Successive Treaties – Vienna conventions -  international law